Association Between Inflammation, Incident Heart Failure, and Heart Failure Subtypes in Patients With Rheumatoid Arthritis. Issue 5 (12th December 2022) - Huang, Sicong; Cai, Tianrun; Weber, Brittany N.; He, Zeling; Dahal, Kumar P.; Hong, Chuan; Hou, Jue; Seyok, Thany; Cagan, Andrew; DiCarli, Marcelo F.; Joseph, Jacob; Kim, Seoyoung C.; et al.
Abstract : Objective: In rheumatoid arthritis (RA), there are limited data on risk factors for the clinical heart failure (HF) subtypes of HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). This study examined the association between inflammation and incident HF subtypes in RA. Because inflammation changes over time with disease activity, we hypothesized that the effect of inflammation may be stronger at the 5‐year follow‐up than at the standard 10‐year follow‐up from general population studies of cardiovascular risk. Methods: We studied an electronic health record (EHR)–based RA cohort with data pre‐ and post‐RA incidence. We applied a validated approach to identify HF and extract ejection fraction to classify HFrEF and HFpEF. Follow‐up started from the RA incidence date (index date) to the earliest occurrence of incident HF, death, last EHR encounter, or 10 years. Baseline inflammation was assessed using erythrocyte sedimentation rate or C‐reactive protein values. Covariates included demographic characteristics, established HF risk factors, and RA‐related factors. We tested the association between baseline inflammation with incident HF and its subtypes using Cox proportional hazards models. Results: We studied 9, 087 patients with RA; 8.2% developed HF during 10 years of follow‐up. Elevated inflammation was associated with increased risk for HF at both 5‐ and 10‐year follow‐ups (hazard ratio [HR] 1.66, 95% confidence interval [95% CI] 1.12–2.46 and HR 1.46, 95% CI 1.13–1.90, respectively), which is also seen for HFpEF at 5 years (HR 1.72, 95% CI 1.09–2.70) and 10 years (HR 1.45, 95% CI 1.07–1.94). HFrEF was not associated with inflammation for either follow‐up time. Conclusion: Elevated inflammation early in RA diagnosis was associated with HF; this association was driven by HFpEF and not HFrEF, suggesting a window of opportunity for prevention of HFpEF in RA.